Diminished reward circuit response underlies pain avoidance learning deficits in problem drinkers - Thang M. Le; Takeyuki Oba; Chiang-Shan R. Li (NeuroImage: Clinical)
Individuals engaging in problem drinking show impaired proactive pain avoidance. As successful pain avoidance is intrinsically rewarding, this impairment suggests reward deficiency, as hypothesized for those with alcohol and substance misuse. Nevertheless, how reward circuit dysfunctions impact avoidance learning and contribute to drinking behavior remains poorly understood. Here, we combined functional imaging and a probabilistic learning go/nogo task to examine the neural processes underlying proactive pain avoidance learning in 103 adult drinkers. We hypothesized that greater drinking severity would be associated with poorer avoidance learning and that the deficits would be accompanied by weakened activity and connectivity of the reward circuit. Our behavioral findings indeed showed a negative relationship between drinking severity and learning from successful pain avoidance. We identified hypoactivation of the posterior cingulate cortex (PCC), a brain region important in avoidance, as the neural correlate of lower learning rate in association with problem drinking. The reward circuit, including the medial orbitofrontal cortex, ventral tegmental area, and substantia nigra, also exhibited diminished activation and connectivity with the PCC with greater drinking severity and learning deficits. Finally, path modeling suggested a pathway in which problem drinking disengaged the reward circuit. The weakened circuit subsequently induced PCC hypoactivation, resulting in poorer pain avoidance learning. As the learning dysfunction worsened alcohol use, the pathway represents a self-perpetuating cycle of drinking and distress. Together, these findings substantiate a role of reward deficiency in problem drinkers’ compromised proactive avoidance, thus identifying a potential target for intervention aimed at mitigating harmful alcohol use.